New tribal placement for the leafhopper genus Evinus Dlabola (Hemiptera: Cicadellidae: Deltocephalinae), with description of a new species from China - Lu, Lin; Zhang, Yalin; Webb, M. D. (Zootaxa, 2011)
The leafhopper genus Evinus Dlabola is formally transferred from Hecalini to Macrostelini (Deltocephalinae) and is reported from China for the first time. One new species from China, E. macrospinus sp. n. is described and a key to species is provided.